1975
DOI: 10.1093/ajcn/28.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral contraceptive agents on vitamin nutrition status

Abstract: Effects of low estrogen combination type oral contraceptives on some of the biochemical parameters used for assessing vitamin nutritional status were investigated in a group of women who had used the pill for 6 to 12 months. Another group of women was examined initially and then at one or more points of time within the first 6 months of treatment. Following changes were observed in women treated with oral contraceptives: 1) increased excretion of kynurenic acid and xanthurenic acid following tryptophan load; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…For example, in most studies there were no controls for dietary folate intake, vitamin supplement use, smoking, or alcohol use. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] In addition, other factors not considered by many investigators include differences in the specific type of hormone used in the OCs, 58,59 compliance with the OC regimen, 44,58,59 and duration of OC use. 50,58 Folate status in these earlier studies was, in most cases, based solely on a comparison of serum folate concentration between groups of OC users and non-users.…”
Section: Folatementioning
confidence: 99%
See 3 more Smart Citations
“…For example, in most studies there were no controls for dietary folate intake, vitamin supplement use, smoking, or alcohol use. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] In addition, other factors not considered by many investigators include differences in the specific type of hormone used in the OCs, 58,59 compliance with the OC regimen, 44,58,59 and duration of OC use. 50,58 Folate status in these earlier studies was, in most cases, based solely on a comparison of serum folate concentration between groups of OC users and non-users.…”
Section: Folatementioning
confidence: 99%
“…32 More recently conducted studies, designed to evaluate the effect of OC use on folate status, have included measures of RBC folate concentration; however, as with studies measuring only serum folate concentration, the results have been equivocal. [46][47][48]50,51,[60][61][62] In the studies from which it was concluded that OC use negatively affected folate status, none controlled for all potentially confounding variables, including differences in dietary intake and use of folic acid-containing supplements. 46,48,60,62 Of those studies that controlled for dietary intake, with one exception, 62 no difference in RBC folate concentration between OC and non-OC users was detected.…”
Section: Folatementioning
confidence: 99%
See 2 more Smart Citations
“…The vitamin B 6 status of the patients was assessed by measuring the stimulation of EGOT activity in vitro in the presence of excess pyridoxal phosphate (PALP effect). A PALP effect greater than 40% was considered to be evidence of vitamin B6 deficiency, and a PALP value less than 35% was considered to indicate adequate vitamin B6 nutriture (15).…”
Section: Methodsmentioning
confidence: 99%